Interventricular Septum and Posterior Wall Thickness Are Associated With Higher Systolic Blood Pressure. Issue 7 (26th November 2015) - Eliakim‐Raz, Noa; Prokupetz, Alex; Gordon, Barak; Shochat, Tzippy; Grossman, Alon
Abstract : Elevated blood pressure (BP) is a known factor that affects the structure of the left ventricle. The association between left ventricular hypertrophy (LVH) and BP in normotensive individuals is poorly understood. All individuals who underwent routine echocardiography and BP measurements as aircrew candidates for the Israeli Air Force in the years 2006 to 2012 were identified. Participants with normal values were included. Associations between echocardiographic characteristics and BP were studied. A total of 2386 participants were included. Mean systolic BP was 125.31±11.18 mm Hg and mean diastolic BP was 68.69±9.02 mm Hg. Interventricular septal (IVS) thickness was positively correlated with systolic BP ( P <.001, correlation coefficient 0.121) and significantly inversely correlated with heart rate and hematocrit level ( P <.001 for both). Men with evidence of IVS or posterior wall thickening on echocardiography, even within the normal range, may require a closer follow‐up of BP.